Development of Primary and Secondary Healthcare Services in Rajasthan: A Review Study : राजस्थान में प्राथमिक और माध्यमिक स्वास्थ्य सेवाओं का विकासः एक समीक्षात्मक अध्ययन - Gupta, Govind (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The development of healthcare services in Rajasthan is crucial for the state's social and economic structure, particularly in the context of primary and secondary healthcare services. This research paper presents a review study based on the development of primary and secondary healthcare services in Rajasthan. The objective of the study is to examine the current state of the healthcare sector in Rajasthan, government policies, programs, and their effectiveness. This review discusses the role of Primary Health Centres (PHCs) and Community Health Centres (CHCs), the impact of government schemes such as Ayushman Bharat and the Bhama Shah Health Insurance Scheme, and the availability of healthcare infrastructure. Additionally, the study highlights the Public-Private Partnership (PPP) model, unequal access to healthcare services, shortages of doctors, and infrastructure issues. The study’s conclusions suggest that improving healthcare services requires digitalization, administrative reforms, and strengthening the role of community health workers. The purpose of this research is to provide policymakers and researchers with guidelines for improving healthcare services in Rajasthan, enhancing both the quality and accessibility of services in the state. Abstract in Hindi Language: राजस्थान में स्वास्थ्य सेवाओं का विकास राज्य के सामाजिक और आर्थिक ढांचे के लिए महत्वपूर्ण है, खासकर प्राथमिक और माध्यमिक स्वास्थ्य सेवाओं के संदर्भ में। यह शोध पत्र राजस्थान में प्राथमिक और माध्यमिक स्वास्थ्य सेवाओं के विकास पर आधारित एक समीक्षात्मक अध्ययन प्रस्तुत करता है। अध्ययन का उद्देश्य राजस्थान में स्वास्थ्य क्षेत्र की वर्तमान स्थिति, सरकारी नीतियाँ, योजनाएँ, और उनकी प्रभावशीलता का अवलोकन करना है। इस समीक्षा में, प्राथमिक स्वास्थ्य केंद्रों (PHCs) और सामुदायिक स्वास्थ्य केंद्रों (CHCs) की भूमिका, सरकारी योजनाओं जैसे आयुष्मान भारत और भामाशाह स्वास्थ्य बीमा योजना का प्रभाव, तथा स्वास्थ्य अवसंरचना की उपलब्धता पर चर्चा की गई है। इसके अतिरिक्त, इस अध्ययन में सार्वजनिक-निजी भागीदारी (PPP) मॉडल, स्वास्थ्य सेवाओं की असमान पहुँच, डॉक्टरों की कमी, और बुनियादी ढांचे की समस्याओं को भी रेखांकित किया गया है। अध्ययन के निष्कर्ष बताते हैं कि स्वास्थ्य सेवाओं में सुधार के लिए डिजिटलीकरण, प्रशासनिक सुधार और सामुदायिक स्वास्थ्य कार्यकर्ताओं की भूमिका को सुदृढ़ करना आवश्यक है। इस शोध का उद्देश्य राजस्थान में स्वास्थ्य सेवाओं के सुधार के लिए नीति-निर्माताओं और शोधकर्ताओं को दिशा-निर्देश प्रदान करना है, ताकि राज्य में स्वास्थ्य सेवाओं की गुणवत्ता और पहुँच में सुधार हो सके। Keywords: राजस्थान, प्राथमिक स्वास्थ्य सेवा, माध्यमिक स्वास्थ्य सेवा, सरकारी योजनाएँ, स्वास्थ्य अवसंरचना, डिजिटलीकरण, नवाचार, सार्वजनिक स्वास्थ्य नीति